2021
DOI: 10.3390/cells10061469
|View full text |Cite
|
Sign up to set email alerts
|

To Trap a Pathogen: Neutrophil Extracellular Traps and Their Role in Mucosal Epithelial and Skin Diseases

Abstract: Neutrophils are the most abundant circulating innate immune cells and comprise the first immune defense line, as they are the most rapidly recruited cells at sites of infection or inflammation. Their main microbicidal mechanisms are degranulation, phagocytosis, cytokine secretion and the formation of extracellular traps. Neutrophil extracellular traps (NETs) are a microbicidal mechanism that involves neutrophil death. Since their discovery, in vitro and in vivo neutrophils have been challenged with a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 174 publications
0
12
0
Order By: Relevance
“…In fact, inhibition of NETs formation increases the sensitivity of mice and humans to bacterial infections [ 4 , 5 ]. However, increasing evidence shows that NETs also contribute to the aggravation of inflammation [ 6 ], the occurrence of autoimmune diseases [ 7 ], the metastasis and development of cancer [ 8 ] and so on. Due to new detection and imaging methods, the exploration of NETs have expanded from in vitro observation to in vivo organ level, and engaged in many specific disease areas, such as systemic lupus erythematosus, vasculitis, diabetes, thrombosis and lung injury [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, inhibition of NETs formation increases the sensitivity of mice and humans to bacterial infections [ 4 , 5 ]. However, increasing evidence shows that NETs also contribute to the aggravation of inflammation [ 6 ], the occurrence of autoimmune diseases [ 7 ], the metastasis and development of cancer [ 8 ] and so on. Due to new detection and imaging methods, the exploration of NETs have expanded from in vitro observation to in vivo organ level, and engaged in many specific disease areas, such as systemic lupus erythematosus, vasculitis, diabetes, thrombosis and lung injury [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the extracellular bacteria of HK- C. albicans -primed BMDM were significantly decreased. Previous studies have shown that ETs are used as an immune response to kill invading bacteria [ 33 ], which were composed primarily of chromatin DNA, histones, and granule proteins [ 34 ]. In our study, we observed a significantly higher release of DNA and higher expression of citrulline histone 3.…”
Section: Discussionmentioning
confidence: 99%
“…NETs are normally cleared by plasma DNAse 1 followed by removal by macrophages. Inappropriate or delayed clearance of NETs or NET components specifically the associated histones and proteases contribute to pathological conditions like sepsis ( 39 ), thrombosis ( 40 ), transfusion-associated acute lung injury ( 41 ), cancer development and metastasis ( 42 ), autoimmune diseases ( 23 , 43 ), and impaired wound healing ( 44 ) - mostly through induction of INF, proinflammatory cytokines, and the NLRP3 inflammasome ( 45 ). A major mechanism for the cytotoxic properties of histones in NETs is through direct binding to the plasma membrane causing calcium influx and loss of membrane barrier function ( 46 48 ).…”
Section: Neutrophils In Necrotizing Enterocolitismentioning
confidence: 99%
“…To further illustrate their double-edged nature, NETs released in the gut have been shown to reduce the translocation of bacteria and support the healing of the intestinal mucosa. On the other hand, excessive NETs formation can damage the barrier function of the intestinal mucosa and thus play a key role in the development of a variety of intestinal diseases ( 23 , 42 ) ( Figure 1 ).…”
Section: Neutrophils In Necrotizing Enterocolitismentioning
confidence: 99%